Duloxetine Hepatotoxicity: A Case-Series from the Drug-Induced Liver Injury Network - Vuppalanchi, Raj (2010)
BACKGROUND: Case reports suggest that duloxetine hepatotoxicity may arise but risk factors, presenting features, and clinical course are not well-described. AIM: To describe the presenting features and outcomes of 7 well-characterized patients with suspected duloxetine hepatotoxicity. METHODS: Patients enrolled in the DILIN Prospective Study undergo an extensive laboratory and clinical evaluation to exclude competing etiologies of liver injury as well as a standardized assessment for causality and disease severity. RESULTS: Between 1/06 and 9/09, 6 of the 7 cases of DILI attributed to duloxetine were assessed as definite or very likely. Median patient age was 49 years, 6 (86%) were women and the median latency from drug initiation to DILI onset was 50 days. Six patients developed jaundice and the median peak ALT in the 5 patients with acute hepatocellular injury was 1633 IU/L. Ascites developed in 1 patient and acute renal dysfunction in 2 others (29%). All patients recovered without liver transplantation even though 3 had pre-existing chronic liver disease. Liver histology in 4 cases demonstrated varying patterns of liver injury. CONCLUSIONS: Duloxetine hepatotoxicity developed within 2 months of drug intake and led to clinically significant liver injury. A spectrum of laboratory, histological, and extra-hepatic features were noted at presentation.